Morphological Gill Abnormalities in the Larvae of Hydropsychidae (Trichoptera: Insecta) for Assessment of Water Quality Variables - Ninon, Amornrat; On Prommi, Taeng (Journal of Food Health and Bioenvironmental Science, 2023)
The aim of this study was carried out to determine the morphological gill abnormalities in hydropsychid larvae in correlation with water quality in the three streams. Samples were collected in April, August and December 2015. In total, 841 individuals were caught belonging to 10 species. Gill abnormalities consisted of dark spots on the gill tufts and reduced numbers of gill filaments. The proportion of individuals with at least some abnormality (HAI), and the average number of abnormal gill tufts for all individuals (HYI) in the Huai Pakkok stream was higher than in the Huai Kayeng stream and the Huai U-Long stream. Physicochemical water quality was slightly differed in each sampling sites. The correlation between normal and abnormal gill morphology and physicochemical water quality parameters were analyzed. The normal and abnormal of Potamyia phaidra were correlated with conductivity, total dissolved solids, and alkalinity (p<0.05), whereas the Cheumatopsyche lucida were correlated with sulfate (p<0.05). The normal and abnormal of Pseudoleptonema quinquefasciatum and the normal of Hydropsyche brontes were correlated orthophosphate (p<0.05).